The Dervishes of the North : Rumi, Whirling, and the Making of Sufism in Canada - Xavier, Merin Shobhana (Book collections on Project MUSE., 2023)
"The thirteenth-century Muslim mystic and poet Jalal al-Din Rumi (1207-73) is a popular spiritual icon. His legacy is sustained within the mystical and religious practice of Sufism, particularly through renditions of his poetry, music, and the meditation practice of whirling. In Canada, practices associated with Rumi have become ubiquitous in public spaces, such as museums, art galleries, and theatre halls, just as they continue to inform sacred ritual amongst Sufi communities. The Dervishes of the North explores what practices associated with Rumi in public and private spaces tell us about Sufism and spirituality, such as sacred, cultural, and artistic expressions in the Canadian context. Using Rumi and contemporary expressions of poetry and whirling associated with him, the book captures the lived reality of Sufism through an ethnographic study of communities in Toronto, Montreal, and Vancouver. Drawing from conversations with Sufi leaders, whirling dervishes, and poets, Merin Shobhana Xavier explores how Sufism is constructed in Canada, particularly at the nexus of Islamic mysticism, Muslim diaspora, spiritual commodity, popular culture, and universal spirituality. Inviting readers with an interest in religion and spirituality, The Dervishes of the North illuminates how non-European Christian traditions, like Islam and Sufism, have informed the religious and spiritual terrain of Canada."--